Systematic review of craniofacial phenotyping in pediatric obstructive sleep apnea : an approach to standardization of methods - Ismail, Izzati Nabilah Ismail; Ismail, Nor Diyana (Thieme Medical Publishers, Inc., 2025)
Craniofacial phenotyping methods are pivotal in understanding and diagnosing pediatric obstructive sleep apnea (OSA). However, the lack of standardized methods often leads to inconsistencies, hindering the reliability and validity of quantitative analyses in this field. This systematic review aims to evaluate existing craniofacial phenotyping methodologies and their key parameters to propose standardization measures to enhance the reliability and validity of future quantitative analyses on this topic. A comprehensive search of electronic databases was conducted following PRISMA guidelines, resulting in the inclusion of 13 studies. Data extraction focused on the types of phenotyping methods and the parameters or measurements used. Our findings revealed a variation in the phenotyping techniques and a wide array of parameters used across studies, highlighting the need for standardization. The authors proposed a framework of parameters for future evaluation of craniofacial morphologies of pediatric OSA. By standardizing the assessment of these craniofacial morphologies, future research efforts can ensure consistency, facilitating more reliable and valid quantitative analyses in this critical area of study.